Nalini by Day, Nancy by Night - Gulati, Sonali (United States : Sonali Films, 2005)
“Nalini by Day, Nancy by Night” is a documentary on outsourcing of American jobs to India. Told from the perspective of an Indian living in the U.S., the film journeys into India’s call centers, where telemarketers acquire American names and accents to service the telephone support industry of the U.S. The film incorporates animation, live action, and archival footage to explore the complexities of globalization, capitalism, and identity.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films